Copeptin Level as a Biomarker of Diabetic Nephropathy: A Major Microvascular complication in Children and Adolescents with Type 1 Diabetes Mellitus - Anwar Deghady, Sohayla Abdelrahman; Elsharaby, Radwa Mahmoud; Mohamed Elrifaey, Shaymaa; Abdelghaffar Taha , Shereen; Erfan , Adel Ali (Journal of Neonatal Surgery, 2026)
Background: Diabetic nephropathy (DN) is a major microvascular complication of Type 1 diabetes mellitus (T1DM) that may lead to end-stage renal disease. Early biomarkers like copeptin, reflecting kidney dysfunction and vasopressin activity, may improve risk prediction and serve as therapeutic targets. The aim of this work was to evaluate serum copeptin as a biomarker for DN in children and adolescents with T1DM. Methods: This analytical cross-sectional study was carried out on 70 children and adolescents aged from 11 years to 18 years who have 2 to 5 years diabetes duration, both sexes, with T1DM and 20 healthy individuals as control. All patients were subjected to serum copeptin level measurement. Results: In diabetic patients, serum copeptin levels did not differ significantly between sexes (P = 0.649). Serum copeptin levels were higher in patients with elevated blood pressure (P < 0.001) and in those with diabetic neuropathy. Additionally, copeptin levels increased significantly with recurrent DKA episodes, with the highest levels observed in patients with >3 episodes, followed by ≤3 episodes, and no recurrence. No significant association was observed between copeptin levels and family history of diabetes or type of initial presentation. Serum copeptin levels showed significant association with multiple metabolic and renal parameters in diabetic patients. Serum copeptin levels were positively correlated with fasting and postprandial glucose, HbA1c values, LDL, total cholesterol, serum creatinine, and A/C ratio, and negatively correlated with HDL and eGFR. Serum copeptin level showed no significant correlation with hemoglobin, leukocyte count, liver enzymes, thyroid hormones, urea, BUN, anthropometric measures, or insulin dose. Conclusions: There is evidence of increased level of serum copeptin level in patients with type 1 DM especially in long standing diabetes with poor glycemic control